Religion and human rights : an introduction - Witte, John, 1959-; Green, M. Christian (Martha Christian), 1968- (Oxford ; New York : Oxford University Press, 2012)
"The relationship between religion and human rights is both complex and inextricable. While most of the world's religions have supported violence, repression, and prejudice, each has also played a crucial role in the modern struggle for universal human rights. Most importantly, religions provide the essential sources and scales of dignity and responsibility, shame and respect, restraint and regret, restitution and reconciliation that a human rights regime needs to survive and flourish in any culture. With contributions by a score of leading experts, Religion and Human Rights provides authoritative and accessible assessments of the contributions of Judaism, Christianity, Islam, Hinduism, Confucianism, Buddhism, and Indigenous religions to the development of the ideas and institutions of human rights. It also probes the major human rights issues that confront religious individuals and communities around the world today, and the main challenges that the world's religions will pose to the human rights regime in the future"--Provided by publisher.
Foreword / Martin E. Marty -- Introduction / John Witte, Jr. and M. Christian Green -- A Jewish theory of human rights / David Novak -- Christianity and human rights / Nicholas P. Wolterstorff -- Islam and human rights / t
Includes bibliographical references and index.
Keywords: Human rights -- Religious aspects; Religions; Religion and politics; Human rights -- Religious aspects; Religion and politics; Religions; Religion; Menschenrecht; Politik; Religions; Human Rights - Religious Aspects; Religion And Politics